Evaluation of routine care of prurigo nodularis in Germany: retrospective chart review study (ADVANCE PN) - Kiedrowski, Ralph von; Metz, Martin; Weisshaar, Elke; Albrecht, Inka; Schild, Marie; Ständer, Sonja (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and Objectives Knowledge on patient care gaps of prurigo nodularis (PN) is limited. This retrospective chart review (ADVANCE PN) investigated unmet medical needs and gaps in diagnostics, treatment, and management of patients with PN in routine care in Germany. Patients and Methods Medical records for adults newly diagnosed with PN between January 2012 and December 2022 from dermatologic clinics and office-based dermatologists were analyzed. Baseline demographics, treatment patterns, diagnostics, symptoms, patient-reported outcomes (PROs), and disease-specific scores are reported. Results Records of 363 patients from 42 sites were analyzed. Median age (range) was 67 (19-95) years; most patients were female (61.7%), Caucasian (73.4%), and retired (57.3%). Overall, 209 (62.2%) patients had comorbidities (most common: hypertension [28.3%]). Clinically, most patients had nodules (81.1%) or papules (66.7%). PROs, disease-specific scores, and laboratory assessments were performed for 32 (8.8%), 12 (3.3%), and 71 (19.7%) patients, respectively. Topical corticosteroids (TCS) were the most common overall (90.9%) and first-line therapy (84.9%); for second-line therapy, ‘no further treatment’ was most commonly documented (58.6%). Conclusions The findings of ADVANCE PN indicate a high unmet need in the current state of medical care, evidenced by shortcomings in PRO assessment, PN documentation, and adherence to guidelines on PN.
Zuerst veröffentlicht: 08. Juni 2025
Gesehen am 17.09.2025